N-acetylcysteine treatment attenuates the cognitive impairment and synaptic plasticity loss induced by streptozotocin. (25th June 2017) - da Costa, Michael; Bernardi, Jamile; Costa, Lidiane; Fiuza, Tiago; Brandão, Ricardo; Ribeiro, Maria F.; Amaral, Joana D.; Rodrigues, Cecília M.P.; Pereira, Maria E.
Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder pathologically characterized by severe neuronal and glial structural changes and progressive cognitive decline. N-acetylcysteine (NAC) is a well-known pharmacological agent with pro-neurogenic properties and neuroprotective effects. In this study, we evaluated NAC protective effects on cognitive impairment and associated pathological markers in a streptozotocin (STZ)-induced sporadic dementia of AD type mice model. Animals were divided into six groups: I) Sham, II) NAC, III) physostigmine (PHY), IV) STZ, V) NAC + STZ and VI) PHY + NAC. NAC (5 mg/kg) and PHY (0.25 mg/kg) were administrated orally for 30 consecutive days and STZ (2.5 mg/kg) intracerebroventricularly at the first and third days. Novel object recognition (NOR, days 26–27) and Morris water maze (MWM, days 26–30) tasks were assessed to evaluate learning and memory. On the thirty-first day animals were euthanized and brains collected for biochemical analysis. Interestingly, our results showed that STZ treatment induced cognitive impairment in mice in the NOR and MWM tasks. Both NAC and PHY treatments prevented from this impairment. The increase in AChE activity and decrease in pTrkB and MnSOD levels caused by STZ in the cerebral cortex and hippocampus, were prevented by the NAC and PHY treatments. The decrease in SYN, MAP2 and GFAP expressions were also prevented by NAC and PHY treatments. In conclusion, NAC treatment prevented the cognitive impairment induced by STZ, normalizing the AChE activity and rescuing the synaptic plasticity loss. Our results suggest that NAC is a promising therapeutic strategy for the treatment of AD. Highlights: STZ induced cognitive impairment in mice in the NOR and MWM task. STZ increased cerebral cortex and hippocampus AChE activity in mice. NAC prevented the decrease in GFAP, MAP and SYN levels induced by STZ. Cerebral cortex and hippocampus IBA1 levels were unaltered by STZ.